Traditional Knowledge of the Bowhead Whale (Balaena mysticetus) around St. Lawrence Island, Alaska - Noongwook, George; Savoonga, The Native Village of; Gambell, The Native Village of; Huntington, Henry P.; George, John C. (ARCTIC, 2009)
Despite considerable research on the bowhead whale (Balaena mysticetus) in Alaskan waters, relatively little has been conducted in the northern Bering Sea. To help fill this gap, we documented traditional knowledge of bowhead whales held by Yupik whalers of St. Lawrence Island, Alaska. Results include descriptions of the seasonal movements, distribution, and abundance of bowheads near St. Lawrence Island. The bowhead population appears to be increasing, as is the number of young whales seen. Changing environmental conditions are influencing distribution, leading to a somewhat earlier spring migration and a greater presence of whales near the island in winter. Hunters describe two bowhead migration paths near the island. It is unknown whether these two paths are used by two genetically different groups of whales, or whether the animals are simply responding differently to oceanographic conditions or geography. Our findings are consistent with studies of this bowhead population conducted elsewhere and suggest that additional research is needed to determine possible migratory (or genetic) differences between the two migrations of whales seen at St. Lawrence Island. Bien que de nombreuses recherches aient été effectuées sur la baleine boréale (Balaena mysticetus) dans les eaux alaskiennes, peu de recherches ont été réalisées dans le nord de la mer de Béring. Afin de combler ce vide, nous avons pris note des connaissances traditionnelles des chasseurs de baleines yupik en matière de baleines boréales sur l’île Saint-Laurent, en Alaska. Les données obtenues prennent la forme de la description des mouvements saisonniers, de la répartition et de l’abondance des baleines boréales près de l’île Saint-Laurent. La population de baleines boréales semble augmenter, comme c’est aussi le cas du nombre de jeunes baleines. L’évolution des conditions environnementales a des effets sur la répartition des baleines et engendre une migration un peu plus hâtive au printemps de même qu’une plus grande présence de baleines près de ...